2021
DOI: 10.1016/j.metabol.2021.154734
|View full text |Cite
|
Sign up to set email alerts
|

The MafA-target gene PPP1R1A regulates GLP1R-mediated amplification of glucose-stimulated insulin secretion in β-cells

Abstract: The MafA-target gene PPP1R1A regulates GLP1R-mediated amplification of glucose-stimulated insulin secretion in β-cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…For example, Ppp1r1a has almost all transcription activity in β cells (Fig. 3e), which was verified by previous studies [13, 7]. The Rnf130 and 1500009L16Rik genes similarly show significant branching trends that are accurately modeled by the branching ODE (Fig.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…For example, Ppp1r1a has almost all transcription activity in β cells (Fig. 3e), which was verified by previous studies [13, 7]. The Rnf130 and 1500009L16Rik genes similarly show significant branching trends that are accurately modeled by the branching ODE (Fig.…”
Section: Resultssupporting
confidence: 87%
“…u 0 (y) = u init y is a stem cell type u(t 0 (y), par(y)) otherwise (6) s 0 (y) = s init y is a stem cell type s(t 0 (y), par(y)) otherwise (7) Here, par(•) refers to the parent vertex in the transition graph. Note that τ is redefined as τ := t − t 0 (y) for each cell type y, i.e.…”
Section: Branching Odementioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously demonstrated that MAFA and MAFB regulate genes required for glucose-stimulated insulin secretion (GSIS) and are reduced in human T2D islets. 18,19,20,27,28 However, the MAF-regulated genes required for insulin granule exocytosis in human β cells have been poorly investigated. Identification of MAFA…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that mutations in the MAFA gene are causing mature onset diabetes of the young 26 further highlighting the importance of MAFA in human β‐cell function. We and others have previously demonstrated that MAFA and MAFB regulate genes required for glucose‐stimulated insulin secretion (GSIS) and are reduced in human T2D islets 18,19,20,27,28 . However, the MAF‐regulated genes required for insulin granule exocytosis in human β cells have been poorly investigated.…”
Section: Introductionmentioning
confidence: 99%